1986
DOI: 10.1021/i200033a023
|View full text |Cite
|
Sign up to set email alerts
|

Carbon deactivation of Fischer-Tropsch ruthenium catalyst

Abstract: Carbon deactivation of a 0.5 wt % Ru/7-AI203 surface-impregnated catalyst was studied by using a Berty continuous-stirred, gas-solid reactor (CSGSR)-gas chromatograph setup. The experimental variables were as follows: temperature, 473-573 K; pressure, 2-6 atm; weight hourly space velocity, 0.85, 16.5 h_1; H2/CO feed ratio, 3 and 2; and synthesis time, 0.5-5 h. Carbon deposited in a synthesis run was measured by integrating the methane evolution profile during catalyst reduction at 723 K in H2. Significant amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…They showed that the deactivation rate increases with the CO partial pressure, due to an inhibition of CO on H 2 adsorption. Similar effects were also observed by other authors [40,59], although the reason for deactivation was not clearly explained. Bell et al [60] proposed that carbon deposition was the main reason for the catalyst deactivation, while Gupta et al [61] proposed that the formation of di-and tri-carbonyls, more difficult to hydrogenate, is responsible for the deactivation during CO hydrogenation.…”
Section: Macro Reactor Experimentssupporting
confidence: 86%
See 1 more Smart Citation
“…They showed that the deactivation rate increases with the CO partial pressure, due to an inhibition of CO on H 2 adsorption. Similar effects were also observed by other authors [40,59], although the reason for deactivation was not clearly explained. Bell et al [60] proposed that carbon deposition was the main reason for the catalyst deactivation, while Gupta et al [61] proposed that the formation of di-and tri-carbonyls, more difficult to hydrogenate, is responsible for the deactivation during CO hydrogenation.…”
Section: Macro Reactor Experimentssupporting
confidence: 86%
“…Furthermore, Ru-based catalysts are less prone to deactivation than the other methanation catalysts [10], even though some deactivation has been reported in the literature when working with gas feeds containing CO [36]. Sintering of small Ru-particles [37,38] and formation of volatile species as Ru-carbonyls [39] are reported among the possible causes of deactivation, although the most critical deactivation mechanism seems to be the formation and deposition of carbonaceous species, leading to active site blocking [40]. Carbon deposition is strongly affected by the process conditions [41,42] but does not lead to permanent deactivation, since high temperature treatments in hydrogen can restore the initial activity [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…36 Since the adsorption energy of CO (−2.3 eV) is much lower than that of CO 2 (−0.52 eV), 37 preferential adsorption of CO and inhibited CO 2 adsorption on the Ru surface are expected and, thus, a decrease in CO 2 conversion. It was proposed that the formation of strongly adsorbed carbonyl species 11,38 due to the presence of CO might be the dominant factor for catalyst deactivation. Therefore, the mechanism of CO poisoning of the Ru/SiO 2 catalyst was investigated by in situ DRIFTS analysis (to be discussed later).…”
Section: Resultsmentioning
confidence: 99%
“…It is also proposed that the surface carbon species formed by hydrogen-assisted CO dissociation participate in the FT synthesis reaction and as precursor for the species that causes catalyst deactivation. 11,71,72 Recent theoretical studies suggest, however, that the CO dissociation ability is favored on couples of atoms on monoatomic steps being the key requirement for Ru to develop a good FTS catalyst, 73,74 followed by hydrogenation and coupling of CH x fragments 75 or CO insertion. 74 Experimental studies have shown that water presents a positive effect on the reaction rate and selectivity, in part due to its ability to remove surface carbon atoms, 4 and in part because Ru particles around 8 nm perform better than smaller particles for FTS.…”
Section: Discussionmentioning
confidence: 99%